Acid Hydrotropic Fractionation of Lignocelluloses for Sustainable Biorefinery: Advantages, Opportunities, and Research Needs. Issue 15 (14th July 2021) - Zhu, Junyong; Chen, Liheng; Cai, Cheng
Abstract: This Minireview provides a comprehensive discussion on the potential of using acid hydrotropes for sustainably fractionating lignocelluloses for biorefinery applications. Acid hydrotropes are a class of acids that have hydrotrope properties toward lignin, which helps to solubilize lignin in aqueous systems. With the capability of cleaving ether and ester bonds and even lignin‐carbohydrate complex (LCC) linkages, these acid hydrotropes can therefore isolate lignin embedded in the plant biomass cell wall and subsequently solubilize the isolated lignin in aqueous systems. Performances of two acid hydrotropes, that is, an aromatic sulfonic acid [ p ‐toluenesulfonic acid ( p ‐TsOH)] and a dicarboxylic acid [maleic acid (MA)], in terms of delignification and dissolution of hemicelluloses, and reducing lignin condensation, were evaluated and compared. The advantages of lignin esterification by MA for producing cellulosic sugars through enzymatic hydrolysis and lignin‐containing cellulose nanofibrils (LCNFs) through mechanical fibrillation from the fractionated water insoluble solids (WIS), and for obtaining less condensed lignin with light color, were demonstrated. The excellent enzymatic digestibility of maleic acid hydrotropic fractionation WISs was also demonstrated by comparing with WISs from other fractionation processes. The recyclability and reusability of acid hydrotropes were also reviewed. Finally, perspectives on future research needs to address key technical issues for commercialization were also provided. Abstract : Acid hydrotropic fractionation : This Minireview provides a comprehensive discussion on the potential of using acid hydrotropes for sustainably fractionating lignocelluloses for biorefinery applications. The mechanism of hydrotropic dissolution of lignin is reviewed, and the performances of p ‐toluenesulfonic acid and maleic acid are evaluated in terms of delignification, dissolution of hemicelluloses, and reducing lignin condensation.